Ésteres triterpênicos de Himatanthus sucuuba (Spruce) Woodson - Silva, Jefferson Rocha de A.; Rezende, Claudia M.; Pinto, Ângelo C.; Pinheiro, Maria L. B.; Cordeiro, Milade C.; Tamborini, Everaldo; Young, Cláudia M.; Bolzani, Vanderlan da Silva [UNESP] (Sociedade Brasileira de Química, 1998)
Bioactivity-guided fractionation from hexane extract of Himatanthus sucuuba barks utilizing Cladosporium sphaerospermum led to the isolation of iridoids plumericin and isoplumericin, which showed higher inhibition against C. sphaerospermum than the antibiotic nistatin. Besides bioactive iridoids were isolated the inactive triterpenes lupeol cinnamate, alpha-amyrin cinnamate and lupeol acetate.
Triterpenic esters from himatanthus sucuuba (Spruce) Woodson
Keywords: Himatanthus sucuuba; iridoids; triterpenes